IIR QMF-Bank Design for Speech and Audio Subband Coding - Löllmann, Heinrich; Hildenbrand, Matthias; Geiser, Bernd; Vary, Peter (Proceedings of IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (WASPAA), 2009)
A new speech and audio codec has been submitted recently to ITU-T by a consortium of Huawei and ETRI as candidate proposal for the super-wideband and stereo extensions of ITU-T Rec. G.729.1 and G.718. This hierarchical codec with bit rates from 8-64 kbit/s relies on a subband splitting by means of a quadraturemirror filter-bank (QMF-bank). For this, an allpass-based QMF-bank is used whose design and implementation is presented in this contribution. This IIR filter-bank allows to achieve a significantly lower signal delay in comparison to the traditional FIR QMF-bank solution without a compromise for the speech and audio qualit